mRNA accessible site tagging (MAST): a novel high throughput method for selecting effective antisense oligonucleotides - Zhang, Hong-Yan (Oxford University Press, 2003)
A solution-based method, mRNA accessible site tagging (MAST), has been developed to map the accessible sites of any given mRNA in high throughput fashion. mRNA molecules were immobilized and hybridized to randomized oligonucleotide libraries. Oligonucleotides specifically hybridized to the mRNA were sequenced and found to be able to precisely define the accessible sites of the mRNA. A number of ways were used to validate the accessible sites defined by the MAST process. Mapping of rabbit β-globin mRNA demonstrates the efficacy and advantage of MAST over other technologies in identifying accessible sites. Antisense oligonucleotides designed according to the accessible site map of human RhoA and Renilla luciferase mRNA result in knockdown effects that are in good correlation with the degrees of accessibility. The MAST methodology can be applied to mRNA of any length using a universal protocol.